2006
DOI: 10.1177/0739986305286137
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and Drug Use, Abuse, and Dependence in Urban Areas and Colonias of the Texas-Mexico Border

Abstract: This study describes the prevalence of alcohol and drug use, abuse, and dependence among adults on the Texas-Mexico border in 2002-2003. The findings are based on survey responses from a random sample of 1,200 adults living in households in three communities: El Paso, a densely populated city in west Texas; the less dense urbanized areas of the lower Rio Grande Valley in south Texas; and rural or semirural colonias—unregulated settlements characterized by lack of basic public services—in south Texas. The findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 16 publications
3
72
0
Order By: Relevance
“…Research consistently shows that foreign-born individuals initially demonstrate better health than their native U.S.-born counterparts, and this is consistent across socioeconomic status and educational attainment (Warner et al, 2006;Maxwell, 2006;Paterson et al, 2006;Wallisch and Spence, 2006;Deren et al, 2005;Berk et al, 2000). With increased time in the United States, the health status of foreign-born individuals tends to deteriorate.…”
Section: Definition Of the Problemmentioning
confidence: 84%
See 2 more Smart Citations
“…Research consistently shows that foreign-born individuals initially demonstrate better health than their native U.S.-born counterparts, and this is consistent across socioeconomic status and educational attainment (Warner et al, 2006;Maxwell, 2006;Paterson et al, 2006;Wallisch and Spence, 2006;Deren et al, 2005;Berk et al, 2000). With increased time in the United States, the health status of foreign-born individuals tends to deteriorate.…”
Section: Definition Of the Problemmentioning
confidence: 84%
“…Although increasingly more research is appearing on substance use among Hispanics in the United States (e.g., Warner et al, 2006;Maxwell, 2006;Patterson et al, 2006;Wallisch and Spence, 2006;Deren, Shedlin and Decena, 2005;Shedlin, Decena, and Oliver-Velez, 2005;Vega, Gil, and Kolody, 2002;Alvarez and Ruiz, 2001;Berk et al, 2000;De la Rosa, Khalsa, and Rouse, 1990), qualitative and epidemiological data on substance use among populations living on the U.S.-Mexico Border are sparse (Wallisch and Spence, 2006;Frost, et al, 2007;Ramos, Ferreira-Pinto, and Ramos, 1998). Given national, state, and local discourse on immigration reform and its impact on immigrants with substance user treatment needs, research that contributes to understanding how immigration policies are perceived by immigrants and how such policies affect their utilization of substance user treatment programs is needed.…”
Section: Definition Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, a number of studies have focused on alcohol and substance use at the city level. One study, using a sample of 400 Hispanics in El Paso in 2002-2003, found that the estimated rates for lifetime, last month, and abuse and dependence for alcohol (81.1, 43.7, 11.8 %, respectively) and drug use (33.2, 4.7, 4.0 %, respectively) were similar to those at the state and national levels [20]. An earlier study of predominantly Hispanic college students in El Paso found that over half were currently drinking alcohol, and nearly a quarter were using other illegal drugs [21].…”
Section: Introductionmentioning
confidence: 58%
“…It was measured based on responses to the following prompt: "On how many occasions (if any) have you had beer, wine or hard liquor during the past 30 days?" Prior research has identified binge drinking as a measure of problem drinking (Wallisch & Spence, 2006;Higgins, Tewksbury & Mustaine, 2007). We measure binge drinking using a dummy variable derived from the self-reported number of times that a student engaged in binge drinking in the past two weeks.…”
Section: Dependent Variablesmentioning
confidence: 99%